2021
DOI: 10.21037/qims-20-825
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy CT quantitative parameters for the differentiation of benign from malignant lesions and the prediction of histopathological and molecular subtypes in breast cancer

Abstract: Background: Dual-energy computed tomography (DECT) is widely used to characterize and differentiate tumors. However, data regarding its diagnostic performance for the characterization of breast tumors are limited. In this study, we assessed the diagnostic performance of quantitative parameters derived from DECT in differentiating benign from malignant lesions and predicting histopathological and molecular subtypes in patients with breast cancer.Methods: Dual-phase contrast-enhanced DECT of the thorax was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Quantitative iodine parameters have been considered a promising tool for distinguishing malignant from benign tumors (12)(13)(14)(15). Spectral curves and the effective atomic number (Z eff ) have helped identify benign and malignant tumors, histological type, and differentiation degree (16)(17)(18)(19). Quantitative dualenergy CT (DECT) analysis has distinguished invasive adenocarcinoma from noninvasive or minimally invasive adenocarcinoma among pulmonary ground-glass opacity nodules (13).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative iodine parameters have been considered a promising tool for distinguishing malignant from benign tumors (12)(13)(14)(15). Spectral curves and the effective atomic number (Z eff ) have helped identify benign and malignant tumors, histological type, and differentiation degree (16)(17)(18)(19). Quantitative dualenergy CT (DECT) analysis has distinguished invasive adenocarcinoma from noninvasive or minimally invasive adenocarcinoma among pulmonary ground-glass opacity nodules (13).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to prior research (11), we used multiple quantitative parameters extracted from DECT. We extracted and calculated 12 features per lesion and used eight machine learning algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…DECT can provide various quantitative parameters for objective quantitative analysis of breast tumors while screening for lung metastases and inflammation lesions compared with mammograms and ultrasounds. Currently, some studies have investigated the role of DECT in the diagnosis of breast cancer via multiple quantitative parameters (11). One study using DECT quantitative parameters showed that the iodine concentration was higher in breast tumors than in the pectoral muscle and normal breast tissue (12).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study (20) showed that vasculature remodeling or neoangiogenesis is an initiating event in the early stage of tumor development; iodine distribution in the tissue is strongly related to local blood volume and vascular density. Therefore, NIC may be used as a surrogate imaging marker for assessing angiogenesis in breast cancer (21) . Studies have shown that there is no statistical significance between the measured iodine content and the true value (22) .…”
Section: Discussionmentioning
confidence: 99%